DESIGNING ENGLISH LEARNING MATERIAL THROUGH VIDEO FOR FOOD AND BEVERAGES (Research and Development to Student of SMK Negeri 5 Pontianak) - Nova - Asteria; Finny - Anita; maliqul - hafis (Journal of English Language Teaching and Education (JELTE), 2024)
This research aims to examine the learning needs and feasibility of English skills in food and beveragepositions at SMK Negeri 5 Pontianak. The method used is research and development (R&D) with afocus on creating learning videos using Canva Pro and kine master applications. The ADDIEdevelopment model guides a systematic process through the stages of Analysis, Design, Development,Implementation, and Evaluation. Purposive sampling involved class XI Hospitality Business Servicesand Tourism Students. Data analysis uses interviews, questionnaires, and validation by media,language, and material experts. The results show that the video developed is an appropriate learningmedium, supporting different learning materials. The stages of the ADDIE model consist of analysis,design, development, implementation, and evaluation carried out to improve the quality of Englishlanguage learning videos on food and beverage positions at SMK Negeri 5 Pontianak.